-3y-15=9y+21

Simple and best practice solution for -3y-15=9y+21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3y-15=9y+21 equation:


Simplifying
-3y + -15 = 9y + 21

Reorder the terms:
-15 + -3y = 9y + 21

Reorder the terms:
-15 + -3y = 21 + 9y

Solving
-15 + -3y = 21 + 9y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-9y' to each side of the equation.
-15 + -3y + -9y = 21 + 9y + -9y

Combine like terms: -3y + -9y = -12y
-15 + -12y = 21 + 9y + -9y

Combine like terms: 9y + -9y = 0
-15 + -12y = 21 + 0
-15 + -12y = 21

Add '15' to each side of the equation.
-15 + 15 + -12y = 21 + 15

Combine like terms: -15 + 15 = 0
0 + -12y = 21 + 15
-12y = 21 + 15

Combine like terms: 21 + 15 = 36
-12y = 36

Divide each side by '-12'.
y = -3

Simplifying
y = -3

See similar equations:

| 2.7x=8.64 | | y+2=6y-13 | | x^2-20d+99=0 | | 4x+7=-6+2x+25 | | -4(2-3x)=3(2x-1)+5 | | 15(p+3)+12=27p+45 | | -54=-9g | | 18=x/10 | | x-4x+3=-27 | | D=2r | | x^3-20d+99=0 | | 6m-3(-4+m)=7m+32 | | x(4x-3)+x(2x-3)=(6x+7)(x-2) | | -(2x+2)-1=-x-(x+3) | | -108=12b | | |x|=-3 | | 2(3-x)=-2(x-4) | | 5x-10=2x+35 | | 3y^5+81y^2= | | -125=5x-3(-4x+2) | | 5+3x+4x=19 | | -4y+12y=16 | | 2x-8+3x=5x-4 | | -2x^2+6x+4=y | | -3/2= | | 21X-3=15X+15 | | 3x(x-6)=11+(x-1)(3x-1) | | 3ax-4y=8 | | -1(-5-6x)=4(5x+3) | | 2k+8=-5(k-3) | | n+7=3N-1 | | -0.16p-0.05(5-5p)=0.05(p-3)-0.1 |

Equations solver categories